Different neural crest populations exhibit diverse proliferative behaviors. Issue 3 (15th September 2014) - Gonsalvez, David G.; Li‐Yuen‐Fong, Mathew; Cane, Kylie N.; Stamp, Lincon A.; Young, Heather M.; Anderson, Colin R.
ABSTRACT The rate of proliferation of cells depends on the proportion of cycling cells and the frequency of cell division. Here, we describe in detail methods for quantifying the proliferative behavior of specific cell types in situ, and use the method to examine cell cycle dynamics in two neural crest derivatives—dorsal root ganglia (DRG) using frozen sections, and the enteric nervous system (ENS) using wholemount preparations. In DRG, our data reveal a significant increase in cell cycle length and a decrease in the number of cycling Sox10+ progenitor cells at E12.5–E13.5, which coincides with the commencement of glial cell generation. In the ENS, the vast majority of Sox10+ cells remain proliferative during embryonic development, with only relatively minor changes in cell cycle parameters. Previous studies have identified proliferating cells expressing neuronal markers in the developing ENS; our data suggest that most cells undergoing neuronal differentiation in the developing gut commence expression of neuronal markers during G2 phase of their last division. Combined with previous studies, our findings show that different populations of neural crest‐derived cells show tissue‐specific patterns of proliferation. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 75: 287–301, 2015